Developing Instrument Evaluation in Teaching Reading Using KAHOOT Applicant for Senior High School - Nurhasanah Auliyani; Sumarsih Sumarsih (TRANSFORM : Journal of English Language Teaching and Learning, 2021)
The purpose of this study is to find out how the feasibility of evaluation tools using KAHOOT application and how students respond to the evaluation tools to be developed. The research method used is research and development (R&D) method using the research model of test instrument development. Research instruments used in the form of tests and questionnaires. This research consists of five steps: 1) Gathering data and information, 2) Need analysis, 3) Developing the instrument evaluation, 4) Validating the product, 5) Revising product and presented as a final product. The average score for student works from the mean value from all aspects is 3.6. It could be concluded that the worksheet is categorized as “Very Good” since the position of the mean value was in the interval 3.25 ≤ ???? ≤ 4.00.